Application of Conventional and Improved Techniques in Felling and Skidding to Residual Stand Damages - Yuniawati; Andini, Sarah; Herni Ningrum, Mutia (Institut Pertanian Bogor (IPB University), 2023)
Felling and skidding are essential in the timber extraction process. But on the other hand, residual stand damage can’t be avoided. This study aimed to analyze the impact of conventional and improved felling and skidding techniques on residual stands in natural forests. Three observation plots were developed to identify the types, numbers, and criteria of residual stand damage due to both techniques. The criteria were categorized as a) minor damage (<25%), b) moderate damage (25–50%), and c) major damage (>50%). It showed that the conventional felling and skidding technique caused damages of 14.92% dominated by tree crown damage and 16.70% dominated by stem wounds, respectively. The residual stand damage due to conventional felling and skidding technique was 31.62% categorized as medium damage. Meanwhile, improved felling and skidding techniques caused damage of 9.89% dominated by broken trees, and 10.27% dominated by stem wounds, respectively. The residual stand damage due to improved felling and skidding technique was 20.16% categorized as minor damage. The improvement techniques can minimize residual stand damage by 36.24%. Therefore, a good understanding of forest concessionaires regarding RIL principles is necessary for achieving sustainable timber harvesting